2000
DOI: 10.1007/s003300000549
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of different protocols for imaging a patient with acute flank pain

Abstract: The aim of this study was to analyse the costs of different diagnostic approaches to patients with acute flank pain. Four different diagnostic approaches were considered: (a) spiral CT without contrast medium (CM); (b) plain film, ultrasonography (US) and intravenous urography (IVU)--the latter procedure is used in our department in cases still unsolved following the former investigations (28% in our experience); (c) plain film, US and spiral CT without CM (as an alternative to IVU in 28% of cases); and (d) IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Important factors include the local prevalence of stone disease, medical resources available, relative costs in a particular system, and the merits and limitations of each diagnostic modality (6). Although CT is the gold standard for diagnosis of renal colic, it is not available outside hospital facilities and is costly (7). There are recent concerns regarding the radiation exposure during CT examinations and its indiscriminate use.…”
Section: Discussionmentioning
confidence: 99%
“…Important factors include the local prevalence of stone disease, medical resources available, relative costs in a particular system, and the merits and limitations of each diagnostic modality (6). Although CT is the gold standard for diagnosis of renal colic, it is not available outside hospital facilities and is costly (7). There are recent concerns regarding the radiation exposure during CT examinations and its indiscriminate use.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Thus, unenhanced helical CT is currently the imaging test of choice for evaluating patients with acute fl ank pain for whom the clinical diagnosis is uncertain. [22][23][24][25][26][27][28][29] In the CT evaluation of ureteral calculi, the agreement between the group of senior residents and the consensus among the abdominal radiologists were very good, as shown in Table 3. The interobserver agreement for identifying the ureteral stone was almost perfect (k = 0.81).…”
Section: Ureterovesical 47%mentioning
confidence: 92%
“…Its use is limited if there is no pyelocaliectasis, and it cannot differentiate between obstructive and nonobstructive dilatation of the renal collecting system. 5,7,[10][11][12][13][14] Studies have shown that 2 hours after onset of a renal obstruction, renal vascular resistance (RVR) increases and renal blood flow (RBF) decreases. [15][16][17][18] Doppler sonography can provide information about these hemodynamic changes.…”
mentioning
confidence: 99%
“…1 Sonography is reportedly an accurate (with 90% sensitivity and 65-84% specificity) and noninvasive method for evaluating the renal collecting system and commonly is used as the first-line imaging modality in cases of suspected renal obstruction. [2][3][4][5][6][7][8][9][10] Although gray-scale sonography may provide important anatomic information, it lacks the ability to provide functional data. Its use is limited if there is no pyelocaliectasis, and it cannot differentiate between obstructive and nonobstructive dilatation of the renal collecting system.…”
mentioning
confidence: 99%